MODEL OF STUDENTS' «IMMERSION» IN INNOVATIVE PROFESSIONAL ACTIVITY - Vitkovskaya, Irina; Solovyeva, Tatiana; Ovchinnikova, Aleksandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The main objective of this paper is to present the authors’ experience in preparing students doing the Primary Education course to implementation of innovative educational technologies in their professional activity. The article describes model of learning activity organization for students (future teachers) aimed to prepare them for innovative professional activity. This model was developed by the authors. It includes a number of stages: informative-motivational, operational, predictive, organizational and reflective. In this order the students pass the stages, i.e. get deeper understanding of innovative educational technologies applied in modern school lower grades. Each stage of the model uses educational strategies that help students to prepare to innovative activities: “intellectual and developmental teaching”, “Being within content” strategy, “simulation”, etc. Implementation of this model in Pskov State University proved its efficiency. Students that took part in the experiment showed positive dynamics in developing all components of readiness to innovative activity. The article pays special attention to the practical aspect of students’ readiness.